2019
DOI: 10.3390/su11133732
|View full text |Cite
|
Sign up to set email alerts
|

The Passivhaus Standard in the Spanish Mediterranean: Evaluation of a House’s Thermal Behaviour of Enclosures and Airtightness

Abstract: Few houses have been built in the Spanish Mediterranean in accordance with the Passivhaus (PH) standard. This standard is adapted to the continental climates of Central Europe and thorough studies are necessary to apply this standard in Spain, especially in the summer. High relative air humidity levels in coastal areas and solar radiation levels of west-facing façades require adapted architectural designs, as well as greater control of air renewal and dehumidification. A priori, energy consumptions undergo big… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 43 publications
0
10
0
Order By: Relevance
“…It is important to emphasise that there is practically no monitoring of collective housing built under the Passivhaus standard in Spain. Only some studies have been carried out on single-family or semi-detached houses [46][47][48]. This results in a very partial bibliography with little relevant data.…”
Section: Relevant Previous Case Studiesmentioning
confidence: 99%
“…It is important to emphasise that there is practically no monitoring of collective housing built under the Passivhaus standard in Spain. Only some studies have been carried out on single-family or semi-detached houses [46][47][48]. This results in a very partial bibliography with little relevant data.…”
Section: Relevant Previous Case Studiesmentioning
confidence: 99%
“…In a case study carried out on a single-family dwelling in Levante, Spain, in which airtight sheets and strips were used, it was concluded that the losses in the dwelling due to air infiltration are very low, 5.4 kWh/m 2 •year, as a value of 0.49 h −1 at n 50 was obtained in the Blower Door test. The value obtained was very low in relation to conventional housing in that area where the ACH is between 5 and 7 times higher [20].…”
Section: Introductionmentioning
confidence: 60%
“…Figures 12 and 13 show computational fluid dynamics (CFD) results for the summer conditions of both simulated models. The second and final step was adjusting the values of ventilation or the interior air renewal and air infiltrations throughout the building envelope [71]. This was made possible using the data obtained from the meter on monthly energy consumption throughout 2014.…”
Section: Appl Sci 2019 9 X For Peer Review 19 Of 26mentioning
confidence: 99%